2016
DOI: 10.4103/2152-7806.179575
|View full text |Cite
|
Sign up to set email alerts
|

Middle meningeal arteriovenous fistulas: A rare and potentially high-risk dural arteriovenous fistula

Abstract: Background:Middle meningeal arteriovenous fistulas (MMAVFs) are rare lesions with a poorly established natural history. We report our experience with patients with MMAVFs who presented with intracranial hemorrhage.Methods:We reviewed our prospectively maintained endovascular database for patients with MMAVFs, who were treated by embolization during a 15-year period. Hospital and outpatient medical records and imaging studies were reviewed.Results:Nine patients with MMAVFs, who presented with intracranial hemor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 14 publications
0
17
0
Order By: Relevance
“…Therefore, it has been reported that the vessel wall injury of MMA caused by head trauma, craniotomy [ 10 ], or interventional surgery [ 7 , 8 ] can cause MMAVF. However, there are a few reports of idiopathic MMAVF with no history of head trauma, craniotomy, or interventional surgery [ 4 , 12 ]. In these reports, all cases presented with intracranial haemorrhage.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Therefore, it has been reported that the vessel wall injury of MMA caused by head trauma, craniotomy [ 10 ], or interventional surgery [ 7 , 8 ] can cause MMAVF. However, there are a few reports of idiopathic MMAVF with no history of head trauma, craniotomy, or interventional surgery [ 4 , 12 ]. In these reports, all cases presented with intracranial haemorrhage.…”
Section: Discussionmentioning
confidence: 99%
“…There are rare reports of MMAVF spontaneously disappearing [ 11 , 12 ]. On the other hand, Rami et al [ 4 ] reported nine cases of MMAVF, which were all caused by intracranial haemorrhage, and mentioned that both traumatic and idiopathic MMAVF should be considered high-risk lesions that require treatment. Additionally, Kitahara et al [ 6 ] reported a case of cavernous sinus syndrome that occurred by the drainage root of MMAVF.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although there are many reports of traumatic or iatrogenic MMAVF cases, only nine spontaneous cases reported in English translation have been found (Term; "middle meningeal arteriovenous fistula" or "middle meningeal artery fistula"). 1,2,[9][10][11] We summarize those characteristics in Supplementary Tables 1 and 2.…”
Section: Spontaneous Mmavf and Its Treatmentmentioning
confidence: 99%